A novel five-level inverter topology for DTC induction motor drive - Sekhar, O. Chandra; Chandra sekhar, K. (2012 IEEE International Conference on Advanced Communication Control and Computing Technologies, 2012)
A novel multilevel control structure for induction motor based on the Direct Torque Control (DTC) strategy using a Five-level Multi Point Clamped (MPC) Voltage Source Inverter (VSI) is presented. It is shown that the multilevel topology presents enough degrees of freedom to control both electromagnetic torque and stator flux with very low ripple and high dynamics on other side. From the simulation results shows that feeding electrical drive with multi level inverter can greatly improves the drive performance. The performance of this control method has been demonstrated by simulations performed using a versatile simulation package, Matlab/Simulink.